The modeling of LED’s disposition - Dabulytė, Jurgita; Ivanauskas , Feliksas; Žukauskas, Artūras (Lietuvos matematikos rinkinys, 2004)
The goal of this work is to construct the scheme of constructing light – emitting diodes system. The mathematical model was written for a light-emitting diodes lamp. The finite difference technique was used for the discretization of mathematical model.